The Instructional Design for Teaching of ReadingSkill at Grade X, SMA N 2 Pati: Naturalistic Study - Wiyati, Sri Ambar, Prof. Dr. Endang Fauziati, M. Hum, Agus Wijayanto, Ph.D (2014)
Reading is important skill as a means of developing second language competence. Those who read more will have larger vocabulary. As the result, they do better on test of grammar, writer better and spell better (Krashen, 1993). English teachers take a central role to help the students to achieve the reading competence, so they need knowledge of instructional design. This study was conducted to describe the instructional design for teaching of reading skill at Grade X, SMA N 2 Pati. The data of this study were the reading teaching learning of two English teachers at grade X, teachers' and students' interview. Each English teacher was recorded twice. The instructional design for teaching reading were: 1)the learning objectives, 2)the syllabus, 3)classroom procedure, 4)classroom reading techniques, 5)the instructional material, 6)teacher's role, 7)student's role, 8)media, 9)assessment. The data were analyzed based on the theories of instructional design components from Richards and Rodgers (1987: 146) in Fauziati (2009: 17-20), Fauziati (2010: 191- 192, 207), Moore and Kearsley (1996), Harmer, J. (2004: 56-63, 78-79, 295-300). Meanwhile, classroom reading strategies were analyzed from Brown H. D. (2000). The result shows first that the components of instructional design for teaching reading at grade X, SMA N 2 Pati that have applied based on the theory: the learning objectives, the syllabus, classroom procedure, classroom reading techniques, teacher's role, student's role, media, assessment. Second, one of the teacher sometimes selected instructional material not related with syllabus. The nine components of instructional design were only one that was not properly done, so it concluded that instructional design for teaching reading at grade X, SMA N 2 Pati has been done well. This findings of the study will hopefully give contribution to improve delivery of instruction and makes the teaching learning of reading effective, efficient.